Is Renal Thrombotic Angiopathy an Emerging Problem in the Treatment of Ovarian Cancer Recurrences? - Kwa, Maryann; Baumgartner, Robert; Shavit, Linda; Barash, Irina; Michael, Jeffrey; Puzanov, Igor; Kopolovic, Juri; Rosengarten, Ora; Blank, Stephanie; Curtin, John P.; Gabizon, Alberto; Muggia, Franco (The oncologist (Dayton, Ohio), 2012)
Learning Objectives After completing this course, the reader will be able to: Describe the need for additional vigilance regarding renal dysfunction when platinums, pegylated liposomal doxorubicin, bevacizumab, and gemcitabine are used for prolonged treatment of recurrent ovarian cancer in combination or sequentially following pre‐existing renal damage. Describe and quantify the risk of chronic kidney disease in patients treated for ovarian cancer. This article is available for continuing medical education credit at CME.TheOncologist.com Background and Objective. Ovarian cancer is usually diagnosed at an advanced stage, with most patients undergoing surgery followed by platinum‐ and taxane‐based chemotherapy. After initial clinical remission, the majority recur, leading to additional treatments, including not only platinums and taxanes but also pegylated liposomal doxorubicin (PLD), gemcitabine, topotecan, and, more recently, bevacizumab, which may extend survival times. PLD, in particular, has been extensively studied by our group, with encouraging therapeutic results. We, however, observed instances of chronic kidney disease (CKD) developing among patients who received long‐term treatment for recurrent ovarian cancer. To document the frequency and contributing factors to the emergence of CKD, we initiated a retrospective review at two institutions. Patients and Methods. Fifty‐six consecutive patients with recurrent ovarian cancer receiving treatment at New York University Cancer Institute were reviewed for the presence of renal disease in 1997–2010. At Shaare Zedek Medical Center, 73 consecutive patients with ovarian cancer were reviewed in 2002–2010. Patients were diagnosed with CKD if they had an estimated GFR <60 mL/minute per 1.73 m2 for >3 months and were staged according to the National Kidney Foundation guidelines. Results. Thirteen patients (23%) developed stage ≥3 CKD. Three patients had renal biopsies performed that showed thrombotic microangiopathy. Conclusions. CKD is emerging as a potential long‐term consequence of current chemotherapy for recurrent ovarian cancer. 摘要 背景与目的. 卵巢癌通常在诊断时疾病就已处于晚期，大多数患者接受手术序贯基于铂类或紫杉类的化疗。初始临床缓解后大多数患者会复发，从而需要接受其他治疗，这些治疗不仅包括铂类和紫杉类，而且包括聚乙二醇脂质体多柔比星 （PLD）、吉西他滨和拓扑替康，以及新近使用的可能延长生存期的贝伐珠单抗。特别是PLD已被我们小组进行了广泛的研究，得出了令人鼓舞的治疗结果。然而，我们在因复发性卵巢癌接受长期治疗的患者中观察到了发生慢性肾脏疾病（CKD）的病例。为了明确CKD的发生频率和相关因素，我们在2个机构进行了一项回顾性分析。 患者与方法. 56例在纽约大学癌症研究所接受治疗的连续入组的复发性卵巢癌患者被用来评估1997 ˜ 2010年肾脏疾病的发生情况。在Shaare Zedek医学中心，73例连续入组的卵巢癌患者被用来评估2002 ˜ 2010年肾脏疾病的发生情况。如果估算的肾小球滤过率（eGFR）< 60 mL/min/1.73 m2且持续时间> 3个月，并依据美国肾脏病基金会指南进行分期，患者诊断为CKD。 结果. 13例（23%）患者发生了分期≥3的CKD。3例患者肾活检显示有血栓性微血管病。 结论. CKD是目前接受化疗治疗的复发性卵巢癌患者潜在的长期并发症。 A retrospective review at two institutions was conducted to document the frequency and contributing factors to the emergence of chronic kidney disease among patients receiving long‐term treatment for recurrent ovarian cancer.